Acknowledging the historical contributions of Black Youth's civic engagement in society. Issue 5 (31st March 2021) - Webster, Nicole
Abstract: Historical contributions of Black youth voices and actions are overlooked from many of the narratives of youth civic engagement (YCE) literature. Specifically, the histories and stories of African American youth in the United States and Black Caribbean youth in the Anglophone Caribbean. The shared socio and political obstacles these particular groups have encountered throughout history shaped similar paths for their involvement in civic society to address many of these social and racial injustices. The article's premise centers on the need for the YCE literature to acknowledge the historical civic contributions African American and Black Caribbean youth have made throughout history. Fundamental historical civic movements that were designed, developed, and supported by Black youth set the tone of Black youth's civic engagement throughout history. These were shaped and contextualized by three specific macrosystem influences (political suppression, institutional racism, and cultural oppression). When YCE scholars begin to make greater meaning of the foundations and critical work developed by Black youth civic activists, a more comprehensive field emerges. With the acknowledgment and inclusion of civic contributions created and implemented during historical eras, more profound meaning is gained of civic engagement among communities and people who have generally been disenfranchised. Coming to terms with their civic legacies developed from racial injustices provides a more comprehensive depiction of civic engagement as a field and body of literature.